Household treatment cost of breast cancer and cost coping strategies from a tertiary facility in Ghana - Kekeli Kodjo Adanu; Eyram Cyril Bansah; David Adedia; Moses Aikins (Public Library of Science (PLoS), 2022)
Breast cancer is the number one cause of cancer death in women globally. According to the Global cancer registry, there were 2.3 million new cases of breast cancer diagnosed in 2020 worldwide, accounting for 25% of all cancer cases in women. The data on the cost burden of breast cancer on households is limited in Ghana, it is therefore imperative that it is estimated to ensure effective planning and provision of adequate resources for breast cancer treatment. This cost-of-illness study estimates the household treatment cost of breast cancer and the cost coping strategies used by patients. This cost-of-illness study was conducted at the surgical unit (Surgical unit 2) of the Korle Bu Teaching Hospital (KBTH), with 74 randomly selected patients and their accompanying caregiver(s). Data was collected using structured questionnaire on direct, indirect and intangible costs incurred and coping strategies used by patients and their households. The results are presented in descriptive and analytic cost statistics. Most of the patients were aged 40-69 years and were married with moderate education levels. Nearly 57% of patients earn an income of USD 370 or less per month. The average household expenditure was USD 990.40 (medical cost: USD 789.78; non-medical cost: USD 150.73; and indirect cost: USD 50). The publicly provided mechanism was the most utilized cost coping strategy. The direct, indirect and intangible costs associated with breast cancer treatment had significant financial and psychological implications on patients and their households. Moreover, poorer families are more likely to use the publicly provided strategies to cope with the increasing cost of breast cancer treatment.